Interview with Sveva Basirah Balzini (Balthazar, 2021)
Sveva Basirah Balzini is an activist, intersectional and decolonial feminist, trans-feminist and radical feminist. He claims his being a survivor, he deals with victims of violence daily, she is also committed in dissemination regarding rape and consent culture and the creation of safer spaces. Muslim, Islamic feminist and founder of SLUM (Sono L’Unica Mia), anarchist, antispeciesist, politically queer and witch. He is pansexual and non-binary.Sveva’s pronouns are he/she and all along the interview these pronouns have been respected and used alternatively.
Keywords: islamic feminism; radical feminism; intersectionality